On the lack of bound states for certain NLS equations on metric graphs. (November 2016) - Serra, Enrico; Tentarelli, Lorenzo
Abstract: The purpose of this paper is to prove some results on the absence of bound states for certain nonlinear Schrödinger equations on noncompact metric graphs with localized nonlinearity. In particular, we show how the topological and metric properties of graphs affect the existence/nonexistence of bound states. This work completes the discussion initiated in Serra and Tentarelli (2016) and Tentarelli (2016).